Development of a methodology for characterizing reaction kinetics, rheology, and in situ compaction of polyimide prepregs during cure. (March 2020) - Magato, James; Klosterman, Donald
PMR-type polyimide prepregs are challenging to fabricate into high quality composites due to volatiles that are generated and must be removed in situ during processing. The current work was conducted to develop accurate, reliable, and practical characterization techniques of the prepreg rheology, volatile generation, and subsequent volatile removal from the prepreg during composite fabrication. Thermal analysis was used to characterize volatile generation, reaction rates, and rheology. A novel approach was used to measure the thickness of the prepreg in situ during vacuum bag/oven processing using a high-temperature LVDT. Experimental results are presented for the commercially available RM-1100 polyimide/carbon prepreg system, including the reaction rate, rheology, and panel thickness results for a series of heating rates and ply counts. The results show the key interrelationships in these coupled phenomena and how that information can be used to select the optimum temperature of pressure application to minimize the final void content.